Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10103-013-1454-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photodynamic therapy for treatment of basal cell carcinoma in organ transplant recipients

Abstract: Photodynamic therapy (PDT) is an established treatment for superficial basal cell carcinoma (BCC). Organ transplant recipients (OTRs) are at increased risk of BCC. We investigated the efficacy of PDT in OTRs and compared the recurrence rate to the non-transplanted population. We conducted a retrospective casenote review of all patients undergoing PDT for the treatment of BCC in our centre from 2003 to 2013. Three hundred and twenty-two BCCs from 103 patients underwent PDT during this period. There is no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…A further retrospective study found 77.4% clearance using two treatments of MAL-PDT, one week apart. No significant difference was found in recurrence rates of NMSC between OTRs and non-transplant recipients [81]. This was supported by a prospective study of superficial and nodular BCCs in 18 OTRs.…”
Section: Organ Transplant Recipientsmentioning
confidence: 90%
“…A further retrospective study found 77.4% clearance using two treatments of MAL-PDT, one week apart. No significant difference was found in recurrence rates of NMSC between OTRs and non-transplant recipients [81]. This was supported by a prospective study of superficial and nodular BCCs in 18 OTRs.…”
Section: Organ Transplant Recipientsmentioning
confidence: 90%
“…Advantages of PDT include the good or even very good aesthetic outcome and the fact that it can be performed on an outpatient basis. Moreover, treating immunosuppressed patients is also possible . The most significant downside is the pain associated with the procedure.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…BCCs are less frequently studied than SCC and its precursors in the SOTR literature due to the reversal of SCC to BCC ratio from 1:4 in immunocompetent to 3.8:1 in white renal transplant recipients; however, PDT appears to be a good option with 17/18 cleared in a SOTR cohort by Guleng and Helsing (E) which included four nodular lesions (all cleared). BCC recurrence rate after two MAL‐cPDT treatments 2 weeks apart was reported by Collier and colleagues as 22.6% in SOTR (mean time to recurrence 1.3 years) and 15.2% in immunocompetent patients (mean time to recurrence 1.4 years), a nonstatistically significant difference, in a 2015 report which reviewed 23 SOTR and 80 immunocompetent patients (C), with a mean follow‐up time of 3.5 years.…”
Section: Review Of Photodynamic Therapy Outcomes In Solid Organ Transmentioning
confidence: 93%